Evaluating Microbial Contamination of Bakeries, Wheat Flour in Ghaemshahr, Iran - Reyhaneh Gouran; Nazanin Khakipour (Journal of Bioresource Management, 2023)
Although flour is regarded as a safe product from the perspective of microbiology due to its low water activity, it can be a suitable environment for the growth of microorganisms if suitable conditions are provided for their growth and reproduction. The objective of this study was to examine the microbial quality of 82 % and 78 % flours distributed in 5 bakeries in the city of Ghaemshahr. The evaluation of the results of the physicochemical tests on the samples revealed that sample No.5's moisture content (82 % of the flour sample from the bakery E) was significantly higher than other samples, while samples No.2 and No.9 had the lowest moisture levels (82 % of the flour sample from the bakery B and 78 % of the flour sample from the bakery D, respectively; all of the samples' moisture contents were within the standard range. All of the flour samples had microbial contamination, according to the evaluation of the results of the microbial tests performed on them, but sample No.1's (82 % of the flour sample from bakery A) microbial population and sample No.8's mold population were significantly higher than those of the other samples. On the other hand, lower mold contamination was seen in flours with a higher level of extraction. There was no statistically significant difference between the mentioned treatments, and the yeast population was significantly higher in samples No.1 (82 % of the flour sample from bakery A) and No.7 (78 % of the flour sample from bakery B) than in the other samples.